Analisis Beban Pendinginan dengan Metode Cooling Load Temperature Difference pada Ruang Perkuliahan Gedung F Institut Teknologi Kalimantan - Rachman, Fiqriza Hadista; Rizianiza, Illa; Gunawan, Gad; Sa’adiyah, Devy Setiorini (LPPM ITK, 2023)
The era of globalization requires humans to continue to innovate in developing technology. The comfort factors of a room are largely determined by the location, characteristics and activities in it. Determination of the amount of power in the Air Conditioner is carried out based on the amount of cooling load obtained. The method used is data the collection of the outside temperature, the measurement of the area of the component to be calculated, and the heat transfer coefficient for the components used. The results show that the cooling load in the 104F lecture room of 21,133 Watt of equivalent to 72,109 BTU/h. While the cooling load in the 105F lecture room, the results are 13,444 W or equivalent to 45,873 BTU/h. From that finding, it can be concluded that the power of the Air Conditioner used in the two rooms has not covered the amount of existing cooling, because the 104F lecture room has three Air Conditioners whereas one Air Conditioner has a power of 2 PK or equivalent to ±18,000 BTU/h, and 105F have two Air Conditioners with the same power. So that the cooling load of the two rooms is greater than the power of the Air Conditioner used.